Vývoj průmyslu České republiky v 90. letech - Huňáčková, Lenka (Univerzita Pardubice, 2006)
Práce se zabývá vývojem odvětví průmyslu České republiky a jeho konkurenceschopoností v devadesátých letech, zejména v souvislosti se vstupem České republiky do Evropské unie.

The bachelor work deals with development of the Czech Republic´s industry and the competitiveness in the nineties with context of the Czech Republic´s entrance into the European Union.
Development of the Czech republic´s industry in the nineties
Keywords: Industry; Česká Republika; Průmysl; hospodářství; HDP; Investice